2012
DOI: 10.1117/1.jbo.17.12.126013
|View full text |Cite
|
Sign up to set email alerts
|

Optical diffusion performance of nanophosphor-based materials for use in medical imaging

Abstract: Recent technologies, such as nanotechnology, provide new opportunities for next generation scintillation devices and instruments. New nanophosphor-based materials seem to be promising for further improvements in optical diffusion studies. In medical imaging, detector technology has found widespread use, offering improved signal capabilities. However, in spite of many spectacular innovations and the significant research in chemical synthesis on the detective material, improvement in signal quality is still an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…It has been shown theoretically [5,6] and demonstrated in practice [7] that diminishing scattering losses in polycrystalline layers is possible in phosphor bodies of reduced grain sizes well below the (emitted) radiation wavelength. This problem was in depth theoretically treated [8] and it was showed that for phosphors emitting in red the optimal imaging resolution properties are achieved when the phosphor particles are about 200 nm in diameter. Nevertheless, the luminescence efficiency of the scintillating screen at this case gets reduced.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown theoretically [5,6] and demonstrated in practice [7] that diminishing scattering losses in polycrystalline layers is possible in phosphor bodies of reduced grain sizes well below the (emitted) radiation wavelength. This problem was in depth theoretically treated [8] and it was showed that for phosphors emitting in red the optimal imaging resolution properties are achieved when the phosphor particles are about 200 nm in diameter. Nevertheless, the luminescence efficiency of the scintillating screen at this case gets reduced.…”
Section: Introductionmentioning
confidence: 99%
“…One form of luminescent nanomaterials can be found as powder phosphors, i.e., phosphor grains (in submicrometer scale or in nanoscale) embedded within a binding material, which can be successfully applied as radiation to light converters in detectors of medical imaging systems. [8][9][10] The physical and luminescent properties of phosphor materials, used as radiation-to-light converters, affect the optical signal transferred out of the detector and play a critical role in the quality of the image and thus in diagnosis validity. 11,12 Many investigations have previously examined the luminescent properties of phosphor materials by providing experimental measurements, theoretical calculations via analytical models and Monte Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive theoretical treatment applying the Mie scattering theory and Monte Carlo simulations showed that the best imaging performance should be expected from scintillator powders with a particle size greater than 200 nm (Liaparinos, 2012). It should be concluded that there is no advantage of utilizing nanophosphor screens for conventional digital radiography with a resolution lower than 20 lp/mm.…”
Section: Applications Of Nanophosphor Screensmentioning
confidence: 99%